Brookings papers on economic activity, 1982 - Brainard, William C.; Perry, George L.; Burtless, Gary. (Washington, D.C. : The Brookings Institution, 1983)
The two articles in this issue deal with the need to encourage business investment and the desire to return federal program responsibilities to state and local governments. Also, four reports in this issue, cover a range of topics: likely consequences of decontrolling gas prices, financial problems arising from high interest rates and recession, evidence on the productivity slowdown, and the relation between bankruptcies and the financial policies of corporations.
Volume II.
A journal incorporating the papers and discussions presented at meetings of the Brookings Panel on Economic Activity.
Includes bibliographical footnotes.
ne 08/07/2019
Loans
Keywords: Economic activity; Economic situation